Coordination properties of Palladium(II) complex taken as a model of an antitumour agent with some selected amino acids, peptides and DNA constituents - Al-Allousi, Ayser; Khalf-Alla, Perihan A.; Hassan, Safaa S.; Shoukry, Mohamed M. (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
Pd(DHP)Cl2 complex ( DHP = 1,3-diamino-2-hydroxopropane ), was synthesizedÂ and characterized by physico-chemical measurements. The coordination of [Pd(DHP)Â (H2O)2]2+ with some selected bio-relevant ligands as phenylglycine, phenylalanine,Â lysine, valine, ethanolamine, glycineamide, glycylphenylalanine, glycylleucine,Â inosine, guanosine and inosine-5â€™-monophosphate disodium salt was investigated. Stoichiometry and stability constants of the complexes formed are reported at 25 0CÂ and 0.1M ionic strength. The results show the formation of 1:1 complexes with aminoÂ acids. DNA constituents form 1:1 and 1:2 complexes. Peptides form both 1:1Â complexes and the coresponding deprotonated amide species. The effect of chlorideÂ ion concentration on the formation constant of inosine, taken as a representaive of DNA constituents, complex with Pd(DHP)2+ was reported.